Antitumor effects of fecal microbiota transplantation: Implications for microbiome modulation in cancer treatment - Xu, Hui; Cao, Chenxi; Ren, Yuqing; Weng, Siyuan; Liu, Long; Guo, Chunguang; Wang, Libo; Han, Xinwei; Ren, Jianzhuang; Liu, Zaoqu (Frontiers in Immunology, 2022)
Fecal microbiome transplantation (FMT) from healthy donors is one of the techniques for restoration of the dysbiotic gut, which is increasingly being used to treat various diseases. Notably, mounting evidence in recent years revealed that FMT has made a breakthrough in the oncology treatment area, especially by improving immunotherapy efficacy to achieve antitumor effects. However, the mechanism of FMT in enhancing antitumor effects of immune checkpoint blockers (ICBs) has not yet been fully elucidated. This review systematically summarizes the role of microbes and their metabolites in the regulation of tumor immunity. We highlight the mechanism of action of FMT in the treatment of refractory tumors as well as in improving the efficacy of immunotherapy. Furthermore, we summarize ongoing clinical trials combining FMT with immunotherapy and further focus on refined protocols for the practice of FMT in cancer treatment, which could guide future directions and priorities of FMT scientific development.